Effects of Noise Reduction on the Physical and Mental State of Patients with Lumbar Disc Herniation in an Orthopedic Outpatient Clinic - Bin Wang; Cheng Shu; Lirong Bai (Noise and Health, 2025)
Objective This study aimed to explore the effects of noise reduction on the physical and mental state of patients with lumbar disc herniation (LDH) in an orthopedic clinic. Methods: A retrospective analysis was conducted on 120 patients with LDH who received conservative treatment in the orthopedic outpatient clinic of Tsinghua University Hospital from February 2022 to February 2023. The orthopedics department underwent noise reduction renovations in August 2022 and has implemented noise control management since then. Sixty patients admitted before the renovations were assigned to the conventional group, and 60 patients admitted after the renovations were assigned to the noise reduction group. The two groups were compared in terms of noise levels during treatment, subjective negative perceptions of noise, pain level (visual analog scale [VAS] scores), negative emotions (self-rating anxiety scale [SAS] and self-rating depression scale [SDS]], sleep quality (Pittsburgh sleep quality index [PSQI]) and quality of life (36-item short-form health survey [SF-36]) before and after a 2-week treatment. Results: Noise level and negative perception of noise in the noise reduction group were significantly lower than those in the conventional group (P < 0.05). After treatment, the noise reduction group had lower VAS, SAS, SDS, and PSQI scores (P < 0.05) but higher a SF-36 score than the conventional group (P < 0.05). Conclusion: Noise reduction in an orthopedic clinic can reduce pain levels and negative emotions and improve the sleep quality and quality of life of patients with LDH.